FTIR PHYTOCHEMICAL FINGERPRINTING AND ANTIOXIDANT ANLYSES OF SELECTED INDOOR NON-FLOWERING INDOOR PLANTS AND THEIR INDUSTRIAL IMPORTANCE - Chunduri, Jayaprada Rao; Shah, Hetwi R. (International Journal of Current Pharmaceutical Research, 2016)
Objective: phytochemical screening and antioxidant activity analyses of selected indoor plants and to evaluate commercial applications. Methods: Qualitative and quantitative phytochemical analyses of alcoholic and aquatic crude extracts of leaves of selected non-flowering indoor plants were assessed using standard protocols and later compared with FTIR analyses. Antioxidant and antibacterial activities of the extracts were studied Results: Phytochemical analysis of polar solvent extractions of the four selected plants Pedilanthus tithymaloides, Cordyline terminalis, Tradescantia zebrine and Rhoeo discolou. Indicated the presence of tannins in all four varieties terpenoids in 3, flavonols, phytosterols and phenols in two plants, followed by alkaloids. The phytochemical analyses were supported by FTIR reports. Quantitative studies indicated variations in flavonol, tannin and phenols concentrations among the four species. High concentrations of Total flavonols (P. tithymaloides) and Tannins (C. terminalis) were observed. C. terminalis extract showed comparatively highest reducing power followed by R. discolour and P. tithymaloides extracts. Antibiotic Sensitivity Testing indicated P. tithymaloides showed a maximum zone of inhibition compared to R. discolor. C. terminalis plant leaf extract showed a faint zone of inhibition against E. fecalis while others couldnot. Intense colors of C. terminalis and T. zebrine plants could be used as a natural dye as well as pH indicator. Conclusion: The rich concentrations of the tannins from non-flowering indoor plants could be the future option of dyes and dyeing industry as natural colorants as well as pH indicators. These plants were rich sources of phytochemicals (phenols, flavonols, tannins, and phytosterols), with antioxidant and antibacterial activity.